Reestructuración técnico administrativa en la empresa Gold Flower Ltda. (2019)
In the present work, the technical and administrative restructuring was carried out in the company Gold Flower Ltda, producer and marketer of tea and aromatics in order to determine the current situation and generate improvement actions in its technical and administrative processes. Various industrial engineering tools were applied such as method engineering, operations management and production, logistics, administration and financial analysis in order to diagnose the company in its processes through different chapters contained as diagnosis, technical study, administrative study and financial study that were developed over six months, time necessary to analyze the processes and procedures and propose improvement actions. The project was developed directly at the company and at the Fundación Universidad de América.